1997
DOI: 10.1128/jvi.71.11.8582-8591.1997
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin V(H) usage during primary infection of rhesus monkeys with chimeric simian-human immunodeficiency viruses

Abstract: It has been suggested that naive immunoglobulins encoded by the V H 3 gene family interact aberrantly with human immunodeficiency virus type 1 (HIV-1) gp120 via a superantigenic epitope, causing initial expansion and eventual depletion of V H 3-expressing B cells. However, this possibility has not been prospectively assessed during an AIDS virus infection. We determined V H family usage in rhesus monkeys during primary infection with chimeric viruses expressing HIV-1 envelopes on a simian immunodeficiency viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 37 publications
(43 reference statements)
1
1
0
Order By: Relevance
“…The seven λ light chains were coded by four IGLV genes and three IGLJ genes, while the three κ light chain clones were coded by three IGKV genes combined with the same IGKJ gene ( Table 2 ). In accordance with previous reports [ 28 , 29 , 30 , 31 ], the IGHV genes originated mostly from two subgroups (IGHV3 and 4), while the IGHD and the IGHJ genes were more diverse. Interestingly, two of the antibodies isolated from the holotoxin-based vaccine library share the same VDJ-germline genes of the VH, with different VL genes, probably due to the combinatorial assembly of the same VH chain with two different VL chains during library generation.…”
Section: Resultssupporting
confidence: 92%
“…The seven λ light chains were coded by four IGLV genes and three IGLJ genes, while the three κ light chain clones were coded by three IGKV genes combined with the same IGKJ gene ( Table 2 ). In accordance with previous reports [ 28 , 29 , 30 , 31 ], the IGHV genes originated mostly from two subgroups (IGHV3 and 4), while the IGHD and the IGHJ genes were more diverse. Interestingly, two of the antibodies isolated from the holotoxin-based vaccine library share the same VDJ-germline genes of the VH, with different VL genes, probably due to the combinatorial assembly of the same VH chain with two different VL chains during library generation.…”
Section: Resultssupporting
confidence: 92%
“…HIV-1 antigen load could obviously be an influence on antigen-specific IgG-ASCs, but the majority of circulating IgG-ASCs are not specific for HIV-1 antigens yet are sensitive to a lowering in their concentration. Although HIV-1 has been reported to contain a superantigen(s) ( 29 , 30 ), this is controversial and the balance of the evidence is not compelling ( 31 , 32 ). HIV-1 has also been reported to directly activate B cells in vitro ( 33 , 34 ), and in one study this effect was reported to be mediated by the COOH terminus of gp41 ( 35 ).…”
Section: Discussionmentioning
confidence: 99%